2016
DOI: 10.1111/jfir.12096
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Regulatory Compliance for Small Banks Around Crisis‐based Regulation

Abstract: In this article I investigate the regulatory burden for small U.S. banks around major crisis-based regulatory programs using measures of profit, cost, and productivity from 1991 to 2014. After the passage of the Federal Deposit Insurance Corporation Improvement Act, there is little evidence consistent with increased regulatory burden. After the passage of the USA PATRIOT Act, the percentage change in employees was positive, and average pay was higher for small banks. After the passage of the Dodd-Frank Act, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 34 publications
4
37
0
Order By: Relevance
“…This higher regulatory burden on smaller community banks has been well researched by academics, regulators, and practitioners. These sentiments were also confirmed by the Conference of State Bank Supervisors (CSBS) as 85% of bankers surveyed also cited that regulatory costs were important in considering acquisition offers (Dahl & Drew, 2018) This unique data set by Dahl et al (2016) documents surveyed compliance costs collected by the Conference of State Board Supervisors, documenting a clear trend of higher compliance costs in smaller banks after the passage of Dodd‐Frank, supporting similar findings by Cyree (2016). Dahl et al (2016) found heterogeneity of compliance costs as smaller banks faced compliance costs of 8.7% as a percentage of noninterest expenses compared to 2.9% larger banks.…”
Section: Literature Review and Discussionmentioning
confidence: 57%
“…This higher regulatory burden on smaller community banks has been well researched by academics, regulators, and practitioners. These sentiments were also confirmed by the Conference of State Bank Supervisors (CSBS) as 85% of bankers surveyed also cited that regulatory costs were important in considering acquisition offers (Dahl & Drew, 2018) This unique data set by Dahl et al (2016) documents surveyed compliance costs collected by the Conference of State Board Supervisors, documenting a clear trend of higher compliance costs in smaller banks after the passage of Dodd‐Frank, supporting similar findings by Cyree (2016). Dahl et al (2016) found heterogeneity of compliance costs as smaller banks faced compliance costs of 8.7% as a percentage of noninterest expenses compared to 2.9% larger banks.…”
Section: Literature Review and Discussionmentioning
confidence: 57%
“…Indeed, for small banks, it is more expensive to gather environmental impact information, and the technologies that they possess are not always adequate for managing internal processes due to the high investments required. Furthermore, the growing regulatory requirements in the financial sector generate proportionately higher regulatory compliance costs for smaller banks than for other bank size categories (Cyree, 2016). Conversely, larger banks have different target customers to smaller ones, and these customers are more concerned about responsible environmental practices.…”
Section: Resultsmentioning
confidence: 99%
“…In equilibrium, some banks may have a strategy to be active in relationship lending. Thus, these banks may intentionally choose to invest in a lower level of technology (see, e.g., Cyree, , who uses loans per employee as a measure of production effects). Therefore, in the regressions below, I control for the bank's technology investment in two ways.…”
Section: Resultsmentioning
confidence: 99%